Abdominal Compartment Syndrome Secondary to Chronic Constipation - Helene Flageole; Jodie Ouahed; J. Mark Walton; Yasmin Yousef (Case Reports in Pediatrics)
Abdominal compartment syndrome (ACS) is defined as an elevated intraabdominal pressure with evidence of organ dysfunction. The majority of published reports of ACS are in neonates with abdominal wall defects and in adults following trauma or burns, but it is poorly described in children. We describe the unusual presentation of an 11-year-old boy with a long history of chronic constipation who developed acute ACS requiring resuscitative measures and emergent disimpaction. He presented with a 2-week history of increasing abdominal pain, nausea, diminished appetite and longstanding encopresis. On exam, he was emaciated with a massively distended abdomen with a palpable fecaloma. Abdominal XR confirmed these findings. Within 24 hours of presentation, he became tachycardic and oliguric with orthostatic hypotension. Following two enemas, he acutely deteriorated with severe hypotension, marked tachycardia, acute respiratory distress, and a declining mental status. Endotracheal intubation, fluid boluses, and vasopressors were commenced, followed by emergent surgical fecal disimpaction. This resulted in rapid improvement in vital signs. He has been thoroughly investigated and no other condition apart from functional constipation has been identified. Although ACS secondary to constipation is extremely unusual, this case illustrates the need to actively treat constipation and what can happen if it is not.